Karakteristik saus cabai dengan penambahan tepung ubi kayu fermentasi - Fitrah Adelina; Teti Estiasih; Y Erning Indrastuti; Masitah Masitah; Essa Annisa Syadiah; Sudarmin Sudarmin; Reskiati Wiradhika Anwar (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
An important characteristic that influences consumers in choosing sauces is texture. Therefore, fermented cassava flour adds to the chili sauce formula. The selection based on the viscosity of cassava flour increased during the fermentation process. Cassava is also a popular local food-producing starch, easily available at low prices. The study intended to describe chili sauce's physical and chemical properties and obtain the best formula for chili sauce. The experiment turned into a completely randomized design with three replications. The first stage carried out the characterization of fermented cassava flour. In the second stage, chili sauce was formulated, with the factor being the addition of fermented cassava flour concentration (0, 1, 2, 3, and 4%). The chili sauce produced is then characterized by its physical and chemical qualities. The results confirmed that the greatest chili sauce was acquired by adding fermented cassava flour by 4%. The sauce produced a water content of 76,77%, ash of 5,07%, the crude fiber of 0,48%, pH value of 4,59%, total dissolved solids of 21,20 Brix, and brightness value (L*) 33,30, 28,47 redness value (a+), 27,97 yellowish value (b+) and 19,233 cP viscosity. Fermented cassava flour is considerably potential to be used for thickener in chili sauce formulas. This study actualizes diversification of chili and cassava processed-product.